2022
DOI: 10.1111/ijac.14190
|View full text |Cite
|
Sign up to set email alerts
|

Experimental additive manufacturing of green body of SiC/Graphite functionally graded materials by stereolithography

Abstract: Ceramic stereolithography (CSL)-additive manufacturing (AM) technology is used to create a functionally graded ceramic (FGC) green body made of silicon carbide (SiC) and graphite. For the SiC/graphite FGC, the mixing parameters of ceramics powders and ultraviolet (UV) curing resin are improved, and correlations of the resultant slurry curing depth with integrated light intensity are discovered. Therefore, the SiC/graphite FGC-produced green body has no flaws, pores, or cracks on its surfaces. According to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…With an increase in contents of YSZ powders from 5 to 20 wt% in the suspensions, the fracture mechanisms was gradually transferred from intergranular fractures to transgranular fractures, contributing to a higher flexural strength (see Figure 6K,L). 28–30 In addition, as for 3D‐printed sintered ZTA composites, it was observed that grain sizes of alumina notably decreased as content of YSZ powders increased, which was attributed to the restraining effect of fine zirconia particles situated at grain boundaries of alumina grains, which hindered grain growth in alumina 30 . Hence, these findings strongly implied that the grain size of alumina plays a vital role in determining the anisotropy on flexural strength.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…With an increase in contents of YSZ powders from 5 to 20 wt% in the suspensions, the fracture mechanisms was gradually transferred from intergranular fractures to transgranular fractures, contributing to a higher flexural strength (see Figure 6K,L). 28–30 In addition, as for 3D‐printed sintered ZTA composites, it was observed that grain sizes of alumina notably decreased as content of YSZ powders increased, which was attributed to the restraining effect of fine zirconia particles situated at grain boundaries of alumina grains, which hindered grain growth in alumina 30 . Hence, these findings strongly implied that the grain size of alumina plays a vital role in determining the anisotropy on flexural strength.…”
Section: Resultsmentioning
confidence: 77%
“…In addition, relative density of 3D‐printed sintered ZTA ceramic parts is shown in Figure 3D. Compared to sintered ZTA composites printed using the model 1 or 2, relative density was lower with respect to ZTA composite ceramic objects printed in the model 3, which might be imputed to the most printing layers and resultant interlayer defects after sintering process 28 . Besides, for sintered ZTA composites fabricated using ceramic suspensions with different contents of YSZ powders added, no obvious difference in relative density could be observed, as shown in Figure 3D.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabricating new composites with this matter by LAM techniques is so limited. Because the other AM methods like stereolithography and direct light processing are more proper than LAM techniques for fabricating composite structures of SiC 51,52 . However, some admirable works have been done by various research groups.…”
Section: Sic Compositesmentioning
confidence: 99%
“…Because the other AM methods like stereolithography and direct light processing are more proper than LAM techniques for fabricating composite structures of SiC. 51,52 However, some admirable works have been done by various research groups. For example, Wu et al 53 fabricated Si/SiC lattice structures by combining various methods, which can be seen in Figure 16.…”
Section: Sic Compositesmentioning
confidence: 99%